Evaluasi Konten Aplikasi Satusehat Menggunakan Mobile Appalication Rating Scale (Mars) dari Prespektif Generasi Z - Irfantiyardi, Krendi Nurislam; Prabowo, Fajar Sidiq Adi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The Covid-19 pandemic is driving the emergence of many new applications in the healthcare field as innovative solutions for safe and effective healthcare services. The increase in smartphone penetration and internet access in Indonesia, especially among Generation Z (born 1995-2010) who are active internet users for more than seven hours per day, supports this trend. This study evaluated the SatuSehat app using the Mobile Application Rating Scale (MARS) measurement tool. The aim was to provide an overview of government healthcare applications. The results review the features of the SatuSehat app and analyze its quality with MARS. This evaluation helps developers design useful and easy-to-use applications to meet the needs of the community in the future. SatuSehat application scored high in Application Quality variables such as Engagement, Functionality, Aesthetics, and Information, with a score of (4.1/5). The success of this application shows that the transformation from PeduliLindungi to SatuSehat has significantly improved its quality. The MARS evaluation shows that generation Z can rely on this app to manage their health. These results form the basis for further development so that SatuSehat continues to innovate and benefit the health of generation Z as the main users in the future.